Farming and feasting during the Bronze Age–Iron Age transition in Britain (ca. 900–500 bce): multi-isotope evidence for societal change - Madgwick, Richard; Esposito, Carmen; Lamb, Angela L. (Frontiers in Environmental Archaeology, 2023)
The Late Bronze Age saw the rise of a new site type in southern Britain, commonly termed a midden. These vast monumental mounds, some comprising tens of thousands of artefacts/ecofacts dominated by animal bone and ceramics, signal a societal refocus towards agricultural intensification and communal feasting on a grand scale. These sites point to agricultural produce being the mainstay of the economy, with bronze having a reduced social and economic importance. This likely created new regimes of managing landscapes and livestock and new networks and agricultural catchments anchored on the sites. Major questions remain surrounding the strategies employed to enhance agricultural productivity, how landscapes and livestock were managed, and how different sites and regions met these challenges at a time of climatic deterioration. This article employs multi-isotope analyses on domestic and wild fauna to address these questions. It presents carbon, nitrogen, and sulfur (δ13C, δ15N, and δ34S, respectively) isotope analyses on 235 animals from 6 midden sites in 2 major regions of midden accumulation: the Vale of Pewsey in Wiltshire and the Thames Valley. The results demonstrate distinct differences in approaches to maximising agricultural productivity, with varied strategies apparent at a site, species, and regional level. Some sites, such as Potterne and Runnymede, clearly drew domestic fauna from a wide catchment where wide-ranging management and foddering regimes were employed. Other sites, such as East Chisenbury, had a more restricted catchment but a tightly controlled, intensive management regime. These data provide new insights into regional responses to the reorganisation of the economy, landscape use, and developing agricultural networks during the Bronze Age–Iron Age transition in Britain, revealing dynamic and evolving societal change.